Comparative study between transforaminal epidural selective nerve root block versus interlaminar epidural in the treatment of lumbar radicular leg pain - Sadiq, Mohammed; Hussain, Syed Azher; Nayeemuddin, Mohammed (International Journal of Research in Orthopaedics, 2019)
Background: Sciatic neuralgia is a result of nerve root oedema because of the inflammatory, immunological and mechanical factors. Steroid injections play an important role in the management of sciatic radiculopathy. Steroids act by reducing the oedema around the nerve roots and decreasing pain. Locally administered steroids have the advantage of reduced dosage and targeted delivery around the nerve roots. This forms the basis of epidural steroid injections. This can be given around the nerve root in the transforaminal space or in the interlaminar space. There is a paucity of literature comparing the two techniques of epidural steroid injections. We have done a randomized comparative trial, to compare the effectiveness of the two modalities of injection in the management of a single level unilateral foraminal disc herniation. Methods: Patients were randomized in two groups Group A: Transforaminal epidural (SNRB) and Group B: interlaminar epidural. Same dose of steroid was used in each group. Results: Immediate post injection, 2 week and 1 month transforaminal epidural (SNRB) was better compare to interlaminar epidural however at the end of 3 months the difference was not significant (p=0.08). Conclusions: Both transforaminal and interlaminar epidural injection are effective form of treatment in mild to moderate grade of disc disease. Both the technique provide short lasting relief in the symptoms associated with disc pathology, however pain management is better in transforaminal group compared to interlaminar group. Thus these techniques can be considered for delaying surgery and providing intermitant relief.